1997
DOI: 10.1148/radiology.203.1.9122383
|View full text |Cite
|
Sign up to set email alerts
|

Menstrual cycle and age: influence on parenchymal contrast medium enhancement in MR imaging of the breast.

Abstract: Patients showed statistically significantly lower parenchymal enhancement in menstrual cycle days 7-20 than in days 21-6. Patients aged 35-50 years yielded higher parenchymal enhancement than did younger patients and older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
161
6
7

Year Published

1999
1999
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(181 citation statements)
references
References 0 publications
7
161
6
7
Order By: Relevance
“…Since there is a trend to use MRI for screening high-risk young women, diagnostic ambiguity will happen due to the very common condition of FCC identified in the same age cohort. MRI for detection of breast cancer should be performed in the second and third week of the menstrual cycles when FCC shows the weakest enhancement [18]. This will reduce the interference of unusual strong glandular enhancement coming from the FCC tissue and therefore decrease falsepositive diagnostic rate for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Since there is a trend to use MRI for screening high-risk young women, diagnostic ambiguity will happen due to the very common condition of FCC identified in the same age cohort. MRI for detection of breast cancer should be performed in the second and third week of the menstrual cycles when FCC shows the weakest enhancement [18]. This will reduce the interference of unusual strong glandular enhancement coming from the FCC tissue and therefore decrease falsepositive diagnostic rate for breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Since MRI of the breast seems to be especially susceptible for VEGF-induced changes in microvascular functions like vessel permeability, as could be shown by anti-VEGF treatment in nude mice (Pham et al, 1998), it seems reasonable to expect that the hormonal exposure of the breast influences parenchymal contrast enhancement patterns. This may explain why these patterns are changing depending on the stage of the patients' menstrual cycle (Müller-Schimpfle et al, 1997). …”
Section: Discussionmentioning
confidence: 99%
“…The assessment of tissue vascularization by Doppler sonographic measurements of vascular resistance and blood flow velocities suggests differences in vascular patterns between premenopausal and post-menopausal patients, and between tumour and normal breast tissue (Villena-Heinsen et al, 1998). Furthermore, parenchymal contrast enhancement patterns in MRI, which are thought to be caused by increased vessel density and permeability (Buadu et al, 1996), are changing depending on the stage of the patients' menstrual cycle (Müller-Schimpfle et al, 1997). Based upon these observations we hypothesized that the regulation of microvascular functions and angiogenesis in breast tissue, a well known target of ovarian steroid action, is likewise dependent on the hormonal milieu.…”
mentioning
confidence: 99%
“…Considering the menstrual cycle, other studies showed that the lowest BPE occurs during the second week of the cycle while the highest occurs during the first and fourth weeks (10,11). It is recommended to schedule non-urgent breast MRIs during days 3 -14 of the cycle to reduce diagnostic interference (7, 12).…”
Section: Discussionmentioning
confidence: 99%